2007
DOI: 10.1128/aac.01217-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Isavuconazole and Other Antifungal Agents against Candida Bloodstream Isolates

Abstract: Isavuconazole is the active component of the new azole antifungal agent BAL8557, which is entering phase III clinical development. This study was conducted to compare the in vitro activities of isavuconazole and five other antifungal agents against 296 Candida isolates that were recovered consecutively from blood cultures between 1995 and 2004 at a tertiary care university hospital. Microdilution testing was done in accordance with CLSI (formerly NCCLS) guideline M27-A2 in RPMI-1640 MOPS (morpholinepropanesulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 14 publications
10
45
0
Order By: Relevance
“…(13,17). In an experimental neutropenic murine model of disseminated Aspergillus flavus infection, it showed high survival rates (19).…”
mentioning
confidence: 99%
“…(13,17). In an experimental neutropenic murine model of disseminated Aspergillus flavus infection, it showed high survival rates (19).…”
mentioning
confidence: 99%
“…This compound can be administered either orally or intravenously as a prodrug, which then is converted by plasma esterases into the active component (3)(4)(5)(6). Previous in vitro studies have demonstrated potent antifungal activity against both common and uncommon fungal pathogens, including Candida, Aspergillus, non-Candida yeasts, and non-Aspergillus molds (7)(8)(9)(10)(11)(12)(13)(14)(15). Furthermore, isavuconazole significantly reduced the organism burden in kidneys of mice infected with Candida tropicalis and the organism burden in both kidneys and brains of neutropenic mice infected with Candida krusei (16).…”
mentioning
confidence: 99%
“…The in vitro MIC profile of isavuconazole against yeasts and molds has been determined in various studies using the broth microdilution (BMD) method of either the Clinical and Laboratory Standards Institute (CLSI) or the European Committee on Antimicrobial Susceptibility Testing (EUCAST) (7)(8)(9)(10)(11)(12)(13)15); however, only one study provided a "head-to-head" comparison of these two methods for testing isavuconazole and the comparison was limited to testing isavuconazole against Aspergillus flavus (10). To date, there are no studies comparing the activity of isavuconazole against Candida as determined by both CLSI and EUCAST BMD methods.…”
mentioning
confidence: 99%
“…Isavuconazole action includes in vitro activity against Aspergillus and Candida species, although the susceptibility of few clinical isolates has been studied (7)(8)(9)(10)(11)(12)(13). Epidemiological cutoff (ECOFF) values can assist in identifying isolates with raised MICs and/or a greater risk of the presence of a mechanism of resistance.…”
mentioning
confidence: 99%